Strategi Diversifikasi Sumber Pendapatan Masjid untuk Meningkatkan Keberlanjutan Keuangan: Studi kasus pada Masjid Al-Ghufran Kuala Lumpur, Malaysia - Putri, Agnesa Widya; Resmiatini, Erna (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
This study analyzes the revenue diversification strategy of Al-Ghufran Mosque in Kuala Lumpur to support its financial sustainability. This study uses a qualitative method with a case study approach, data collected through interviews, observations, and document analysis. Informants were selected using a purposive sampling technique. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of this study reveal that Al-Ghufran Mosque implements three types of diversification strategies, namely horizontal diversification through business management such as cafes and facility rentals, concentric diversification by utilizing existing assets, and conglomerate diversification through rooftop rentals to telecommunications companies. Implementing this strategy has been proven to help improve the financial sustainability of mosques and reduce dependence on congregational donations. This study confirms that revenue diversification plays an important role in supporting the financial sustainability of mosques, as well as being a reference for the financial management of other mosques.